Sustainable tourism in nature reserves in the Syrian Badia"Talila model" (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Not natural reserves in both the goals and objectives; some of which is dedicated strict protection, especially those that have a scientific interest, some of which is dedicated to attracting visitors and tourist activities and the protection of the environment and cultural values, and this is what is called sustainable tourism, which is one of the most important types of tourism; because they are based primarily to protect the ecological balance, and the contemplation of nature, flora and fauna, and provides human comfort; Vtaatgely feature in sustainable tourism in generating opportunities for local parks, and business in the country, while protecting the environmental and cultural values in the protected areas. From this perspective, research the topic of sustainable tourism treated in Talila protected by shedding light on the development of tourism projects, which is a basic need and economic engine of the state and society at the same time, especially in the Syrian desert, as well as the ability of tourism projects to secure a sustainable financial resources, through answer the following questions: - What positive effects of sustainable tourism in nature reserves? - What is the importance of sustainable tourism in the conservation of natural resources? - How sustainable tourism contribute to raising the attention of local and international political and economic circles in reserves?